The Temperature-Regulation of Pseudomonas aeruginosa cmaX-cfrX-cmpX Operon Reveals an Intriguing Molecular Network Involving the Sigma Factors AlgU and SigX - Bouffartigues, Emeline; Si Hadj Mohand, Ishac; Maillot, Olivier; Tortuel, Damien; Omnes, Jordane; David, Audrey; Tahrioui, Ali; Duchesne, Rachel; Azuama, Cecil Onyedikachi; Nusser, Michael; Brenner-Weiss, Gerald; Bazire, Alexis; et al. (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is a highly adaptable Gram-negative opportunistic pathogen, notably due to its large number of transcription regulators. The extracytoplasmic sigma factor (ECFσ) AlgU, responsible for alginate biosynthesis, is also involved in responses to cell wall stress and heat shock via the RpoH alternative σ factor. The SigX ECFσ emerged as a major regulator involved in the envelope stress response via membrane remodeling, virulence and biofilm formation. However, their functional interactions to coordinate the envelope homeostasis in response to environmental variations remain to be determined. The regulation of the putative cmaX-cfrX-cmpX operon located directly upstream sigX was investigated by applying sudden temperature shifts from 37°C. We identified a SigX- and an AlgU- dependent promoter region upstream of cfrX and cmaX, respectively. We show that cmaX expression is increased upon heat shock through an AlgU-dependent but RpoH independent mechanism. In addition, the ECFσ SigX is activated in response to valinomycin, an agent altering the membrane structure, and up-regulates cfrX-cmpX transcription in response to cold shock. Altogether, these data provide new insights into the regulation exerted by SigX and networks that are involved in maintaining envelope homeostasis.